ORGANIZATION OF IMPLEMENTATION OF PRODUCTION AND EXPORT STRATEGY IN NEWLY ESTABLISHED TEXTILE ENTERPRISES ON THE BASIS OF COOPERATION (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Most newly created textile enterprises begin their production activities and after a certain period of time, as a result of a decrease in the competitiveness of products in the domestic and foreign markets, various economic and social problems arise. This forces some enterprises to temporarily suspend their work or choose another field of activity and even run the risk of bankruptcy. Decree of the President of the Republic of Uzbekistan dated June 9, 2021 № PF-6244 “On additional measures to increase the industrial potential of the regions” was adopted. The decree provides for the expansion and deepening of ties between intra-and inter-industry cooperation, the involvement of enterprises in global production chains, and the establishment of joint exports of manufactured products to third countries.